Diversity patterns and chronobiology of hawkmoths (Lepidoptera, Sphingidae) in the Brazilian Amazon rainforest - Camargo, Amabilio J. A. de; Camargo, Nicholas F. de; Correa, Danilo C. V.; Camargo, Willian R. F. de; Vieira, Emerson M.; Marini-Filho, Onildo; Amorim, Felipe W. [UNESP] (Springer, 2016)
As biodiversity loss rapidly increases through habitat degradation in the Amazon rainforest, the need to characterize and understand the species diversity becomes even more important. In this study we used empirical and published datasets to assess the diversity patterns and produce the first overview of the sphingid fauna in the Brazilian Amazon. We compared the diversity patterns in distinct areas in the biome by analyzing hawkmoth assemblages considering both species composition and abundance, and asked whether these communities are structured according to environmental factors. Additionally, we provide information of diel activity pattern of sphingids and evaluated the importance of time in sampling effort. We found that the Brazilian Amazon may harbor more than 80 % of the hawkmoth species that occur in Brazil and more than half of the species recorded in South America. Species composition and assemblage structure is determined by the quality of the habitat (disturbed or undisturbed vegetation), temperature and relative humidity. Finally, we show that the temporal activity of sphingids presents distinct patterns at different taxonomic levels, highlighting the importance of full night collections to better characterize the fauna. Our results show that habitat alteration can be an important factor affecting sphingid assemblages, illustrating the importance of Protected Areas in species maintenance.
Keywords: Amazon; Hawkmoth assemblage; Lepidoptera; Species richness; Temporal activity; Tropical forest